Female sex work in Yangon, Myanmar - Gillieatt, Sue; Talikowski, Luke (CSIRO Publishing, 2005)
BackgroundMyanmar (Burma), with an upper estimate of 400,000 people living with HIV/AIDS, faces a dangerous and potentially devastating epidemic. Female sex workers in the country are one of the most affected populations with high prevalence rates of both HIV and sexually transmitted infections (33.5% women with HIV in one study population).MethodsA qualitative study was undertaken in Yangon at the end of 2002 to investigate the social and demographic features contributing to the transmission of HIV among female sex workers in urban Myanmar.ResultsThe research findings indicate that female sex workers in Myanmar are marginalised and difficult to access for research enquiry due to a variety of legal, political, cultural and social factors. Their reported rates of unsafe sexual practice, insufficient HIV/AIDS education, social stigmatisation, poor access to and quality of health services as well as inadequate public health programs make them particularly vulnerable to HIV and STIs.ConclusionsThis paper advocates several feasible steps to improve the situation. There needs to be national recognition that the HIV epidemic amongst female sex workers is a priority development problem with major societal implications requiring change to national social norms and values. A sustained partnership must be developed between all key stakeholders, including sex trade representatives, to enable the development and implementation of integrated target-specific HIV/AIDS prevention strategies. Finally, sex workers need to be guaranteed access to basic and general health services providing non-discriminatory and high quality care.